PENGARUH REKRUTMEN DAN SELEKSI, PELATIHAN DAN PENGEMBANGAN, PENILAIAN KINERJA, DAN KOMPENSASI TERHADAP KINERJA ORGANISASI - ASTRIE SEPTININGTYAS; NURWANTI NURWANTI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose from this research is to determine how to influence human resource management practice such as recruitment and selection, training and development, performance appraisal, and compensation to organizational per-formance. The methods which is used on the research is descriptive and casuality. Respondents who in volved in this study is permanent employees with staff level who work for Hoka-Hoka Bento in all branches Bekasi as much as 160 people. This research used saturated sampling technique. The data was obtained from primary data which has been collected through questionnaires with likert scale. The methods of data analys is on this research are simple regression and multiple regression. The result soft his research are variable of recruitment and selection, training and development, performance appraisal, and compensation have positive influence to organizational performance individually. Recruitment and selection is variable that have the most significant impact on organizational performance.